Menanamkan Pendidikan Menabung Sejak Dini Dengan Teori Aspek Kognitif Taksnomoni Bloom - A Khaerul Mu'min; Dany Ramdany (Jurnal Kajian Ilmiah, 2023)
Wasteful nature is experienced by many children today. Whereas Islam provides lessons so that humans avoid wasteful nature. Parents who are busy working make their children's education less focused. parents will be more likely to provide facilities to children so that parents are calmer at work. In fact, in this way, children do not feel empathy for their parents who have worked hard to find money for their children. It is this trait that fosters extravagant behavior so that there are many phenomena of children spending their parents' money. Frugality and saving are characters that are contrary to wasteful nature, with saving being a means of changing the economic system that exists in the family, even the economy in society in general. In this study using a descriptive method with a qualitative approach so that researchers can be more comprehensive in examining the object of research. The conclusion of this study shows that instilling saving education from an early age can be applied by parents and educators at school. This study shows the stages of instilling saving behavior in children who have psychological problems, the result is that children can still be given education with stages that can be used from the theory of cognitive aspects of Bloom's taxonomy. The novelty of this research is that parents or educators can educate their children to save for their future. Saving will change the family economy and even change the economy of a region and country in the future.